2015
DOI: 10.1002/lary.25805
|View full text |Cite
|
Sign up to set email alerts
|

Orbit fractures: Identifying patient factors indicating high risk for ocular and periocular injury

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
57
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 30 publications
7
57
0
14
Order By: Relevance
“…The frequency of associated ocular injuries has been reported to range from 22 to 30%, with most ocular injuries characterized as self-limiting and minor. 5,9,15,16 In the present results, ocular injuries were only found in the elderly patients (5.6%). The rate was rather low compared with the results from Andrews et al 15 or Ho et al 16 These investigators concluded that 10.0 to 26.7% of orbital fractures will include vision-threatening ocular injuries.…”
Section: Discussionsupporting
confidence: 41%
See 4 more Smart Citations
“…The frequency of associated ocular injuries has been reported to range from 22 to 30%, with most ocular injuries characterized as self-limiting and minor. 5,9,15,16 In the present results, ocular injuries were only found in the elderly patients (5.6%). The rate was rather low compared with the results from Andrews et al 15 or Ho et al 16 These investigators concluded that 10.0 to 26.7% of orbital fractures will include vision-threatening ocular injuries.…”
Section: Discussionsupporting
confidence: 41%
“…5,9,15,16 In the present results, ocular injuries were only found in the elderly patients (5.6%). The rate was rather low compared with the results from Andrews et al 15 or Ho et al 16 These investigators concluded that 10.0 to 26.7% of orbital fractures will include vision-threatening ocular injuries. 15,16 One reason for our lower rate of ocular injuries might have been that during the study period, patients were referred for ophthalmologic consultation according to their symptoms.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations